Natureza da tutela da defesa da concorrência e interface com os direitos humanos e transindividuais - Marques, Fernando de Oliveira (2018)
Competition law is a matter of extreme importance as it aims to ensure a competitive and healthy market environment in order to avoid economic concentration and that anticompetitive behavior is detrimental to the market, to the consumers and to society. It should be noted, however, that there is little discussion about the legal nature of competition law. As a way of achieving this objective, the present work has the objective of analyzing the main characteristics of the right of defense of competition in order to verify the great proximity of said institute with human rights and transindividual rights, both with regard to its purposes, and the recipients